A Framework for Variable Quality in Applications through Context-Aware Approximate Computing - Castro, Roberto Alejandro Hidalgo; Wanner, Lucas (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2018: Anais do VIII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2018)
We introduce a framework that enables applications to dynamically change their quality (and consequently their resource usage) according to contextual information and energy consumption goals. The framework combines a multi-implementation mathematical library with a context monitoring system service and an application adaptation support system. The library features multiple implementations of varying quality and cost for each supported function. The context monitoring system service continuously evaluates system resource usage, and signals applications to adapt their quality (by changing to lower or higher quality implementations) when overall energy usage deviates from a goal set by the user. The support system receives information from the monitoring system, and transparently changes the implementations used by applications. Our experiments demonstrate that the framework can save up to 62% in energy consumption by tolerating at most of 4% degradation in application quality. Experiments furthermore show that the framework can successfully reach desired energy goals by dynamically adjusting application quality.